Utilizing E-Commerce Affiliate Programs as a Digital Revenue Diversification Strategy for Halal Products - Dela Safitri; Fahrurrozi Fahrurrozi; Ridan Muhtadi Ridan Muhtadi; Muhammad Zainur Rahman Afandi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The rapid development of the digital economy has encouraged the emergence of various innovations in generating income opportunities, including the utilization of e-commerce affiliate programs as a digital marketing strategy. In the context of the halal industry, this strategy has become increasingly relevant due to the growing demand for halal products and the need for business actors to diversify their sources of income. This study aims to analyze the utilization of e-commerce affiliate programs as a strategy for digital income diversification in halal products. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The informants in this study are affiliate marketers who actively utilize digital platforms. The results show that e-commerce affiliate programs play a significant role as an alternative source of income that is flexible and accessible to various groups. In addition, this strategy is effective in expanding the marketing reach of halal products without requiring high promotional costs. The success of affiliate program implementation is influenced by several factors, including personal branding, content consistency, product selection, and the ability to build consumer trust. This study concludes that e-commerce affiliate programs are a relevant and potential strategy for supporting digital income diversification while strengthening the halal industry ecosystem in the digital economy era.